Unravelling the complexity of the relationship between social support sources and loneliness: A mixed-methods study with older adults - Esteban Sánchez-Moreno; Lorena Patricia Gallardo-Peralta; Vicente Rodríguez-Rodríguez; Pablo de Gea Grela; Sonia García Aguña (PLoS ONE, 2025)
Loneliness is an increasingly significant social and public health issue in contemporary societies. The available evidence suggests that social support is one of the key psychosocial processes for the reduction and prevention of loneliness. This study investigated the role played by sources of social support in the experience of social and emotional loneliness, identifying seven sources of support split between family (spouse/partner, children, grandchildren, siblings) and non-family (friends, neighbours). The study population comprised people aged 65 years and over living in Spain, with a partner (without cohabiting children), alone or in a nursing home. A mixed-methods approach was used, combining data from a survey involving 887 participants (quantitative phase) and data from semi-structured interviews with 30 older adults (qualitative phase). The relationship between the various sources and loneliness was analysed using structural equation modelling (SEM) for the survey data and thematic analysis for the qualitative information. The results from both phases of the study suggest different association dynamics between sources of social support and the social and emotional dimensions of loneliness. Lower levels of emotional loneliness were related to support from the following sources: spouse, children, grandchildren, siblings and friends. Lower levels of social loneliness were related to support from the following sources: spouse, grandchildren, siblings and friends. In contrast, greater levels of emotional loneliness were related to support from neighbours and greater levels of social loneliness were related to support from children. The findings of this study contribute to a better understanding of the association between social support and loneliness and suggest that interventions aimed at reducing loneliness could be more effectively targeted by considering the specific effects of support derived from different sources.